Dekonstruksi Pernikahan: Persepsi Mahasiswa UIN Antasari Banjarmasin tentang Fenomena Childfree - Helmiyah, Fauzatul; Damaiyanti, Varinia Pura (Huma: Jurnal Sosiologi, 2025)
The phenomenon of childfree, which is the decision not to have children in marriage, has attracted increasing attention in Indonesia because it contradicts traditional norms that regard children as a symbol of family perfection. This study aims to explore the views of students at the Islamic State University of Antasari Banjarmasin on the childfree phenomenon and examine how religious and social values shape their meanings and responses to the phenomenon. This research uses a qualitative method with a descriptive approach. Data collection techniques used observation, semi-structured interviews, and documentation. The results showed that UIN Antasari Banjarmasin students have an open view towards childfree choices, although there are significant differences in personal values and perceptions. Some students see childfree as a rational and personal consideration that can be accepted if it is based on careful consideration. Others view childfree as contrary to religious and social norms that emphasise the importance of procreation and family. Social media also plays an important role in disseminating information and forming opinions about childfree, but the final decision is still influenced by personal beliefs and couple agreement. Derrida's deconstruction approach is used to understand the phenomenon of childfree as the formation of new meanings in marriage and family, which challenges traditional norms and opens space for a more inclusive interpretation of individual life choices. This research provides insight into the dynamics between religious values and modernity in university students' views on childfree. Further research is recommended to explore the factors that influence the childfree decision from a gender perspective, as well as analysing the role of social media in shaping opinions about childfree.